Laterality of acute otitis media: different clinical and microbiologic characteristics - McCormick, David P; Chandler, Stephanie M; Chonmaitree, Tasnee (The Pediatric infectious disease journal, 2007)
A large individual patient data meta-analysis recently showed that children aged less than 2 years with bilateral, as compared with unilateral, acute otitis media (AOM) were at higher risk for persistent symptoms without antibiotic treatment. Prior studies have shown a propensity for children with bilateral AOM to be infected with bacterial pathogens, specifically Haemophilus influenzae. The objectives of this study were to further characterize risk factors for bilateral AOM and to assess the propensity for specific viral and bacterial pathogens to predispose to bilateral versus unilateral AOM. We performed a secondary data analysis on 1216 cases of AOM diagnosed and treated at our institution: 566 subjects underwent tympanocentesis and middle ear fluid (MEF) culture. We compared subjects with bilateral and unilateral AOM for demographic characteristics, clinical findings, parent/clinician perception of AOM severity, and MEF study results for bacteria and viruses. When compared with children who have unilateral AOM, children with bilateral AOM were more likely to be younger (P < 0.001), have H. influenzae isolated from one or both MEFs (P < 0.0001), and have more severe inflammation of the tympanic membrane on otoscopic examination (P < 0.0001). Compared with children who have unilateral AOM, children with bilateral AOM are more likely to have bacteria in the MEF and have more severe inflammation of the tympanic membrane. This may help explain why children with bilateral AOM are more likely to experience persistent symptoms without antibiotic treatment. Laterality of AOM should be considered when discussing treatment options with parents.